El «llibre cortés de lectura» en català: a propòsit del manuscrit F-129 del Col·legi de la Sapiència de Palma - Soler, Albert (Caplletra. Revista Internacional de Filologia, 2006)
The manuscript F-129 of the Col·legi de la Sapiència de Palma contains three works of Ramon Llull. It is made up of two separate manuscripts belonging to the first generation of Lullian codices (that is, not later than the first quarter of the fourteenthcentury). This collection is preceded by a remarkable full-page illustration, an analysis of which shows that it was probably based on a similar miniature from a French codex emanating from Llull’s immediate circle. The codicological model applicable to this manuscrit is that of «libro cortese di lettura».